Risk Analysis of a company’s Offshore Wind Farm Assets: A Conceptual and Empirical study of the Development Phase. - Marchand, Boris (2009)
A global energy player design with the University of Nottingham a dissertation placement which aims at providing a risk analysis of the organization’s offshore wind farm assets, particularly at the certain stage of the process labeled “Development”. Therefore, this paper proposes a risk model labeled “Risk Management Process” (RMP) based on risk literature but developed and adapted especially for this research. A review of the literature will contribute in presenting the different steps I have been through to carry out this risk analysis. Using qualitative methods and following the developed model, I identified three major areas of risks. Several risk have then been spotted and measured within these areas which provides a clear picture of what the company is currently facing and will face in the future. Lastly, this research addresses the risks by proposing several recommendations that may be considered to reduce their impacts on the company. The findings and recommendation of this research were presented to the company.